A study on the characteristics of upflow matrix filter materials for the treatment of domestic sewage water. (February 2016) - Li, Xinpeng; Pashley, Richard M.
Abstract: This study was aimed at the development of robust mixed bed upflow matrix filters for use in an in-situ, household sewage treatment and recycling system. Several filter materials were studied to determine their relative filtration properties, measured by their filter coefficient and ability to regenerate via back-washing. Fecal coliforms were used as monitor organism, for direct application to sewage treatment processes. The filter materials included a range of different particle size of smooth, spherical (Ballotini) glass particles, uniform quartz sand particles, activated powdered charcoal, chemically methylated glass particles and alumina particles. An inverse correlation was observed between filter coefficient and potential for regeneration. The surface properties of the powdered materials, such as hydrophobicity, zeta potentials and surface charge densities were found to be important in determining their filtration properties.